Network pharmacology, a promising approach to reveal the pharmacology mechanism of Chinese medicine formula - Zhao, Li; Zhang, Hong; Li, Ning; Chen, Jinman; Xu, Hao; Wang, Yongjun; Liang, Qianqian (Journal of ethnopharmacology, 2023)
Network pharmacology is a new discipline based on systems biology theory, biological system network analysis, and multi-target drug molecule design specific signal node selection. The mechanism of action of TCM formula has the characteristics of multiple targets and levels. The mechanism is similar to the integrity, systematization and comprehensiveness of network pharmacology, so network pharmacology is suitable for the study of the pharmacological mechanism of Chinese medicine compounds. The paper summarizes the present application status and existing problems of network pharmacology in the field of Chinese medicine formula, and formulates the research ideas, up-to-date key technology and application method and strategy of network pharmacology. Its purpose is to provide guidance and reference for using network pharmacology to reveal the modern scientific connotation of Chinese medicine. Literatures in this review were searched in PubMed, China National Knowledge Infrastructure (CNKI), Web of Science, ScienceDirect and Google Scholar using the keywords “traditional Chinese medicine”, “Chinese herb medicine” and “network pharmacology”. The literature cited in this review dates from 2002 to 2022. Using network pharmacology methods to predict the basis and mechanism of pharmacodynamic substances of traditional Chinese medicines has become a trend. Network pharmacology is a promising approach to reveal the pharmacology mechanism of Chinese medicine formula. [Display omitted] •Summarizing therapeutic effect of Chinese medicine formula on different diseases.•Classifying studies according to different diseases.•Summarizing databases, prediction method, validation, mechanisms in tabular form.